Analysis of the Effectiveness of Implementation of Corporate Social Responsibility (CSR) Perisai Bumi by PT. Pertamina Gas in the Kab. Indramayu - Riswandi; Kusumastuti, Tantri; Kharisma, Waode; Furrie, Wulan (PT FORMOSA CENDEKIA GLOBAL, 2024)
One of the Corporate Social Responsibility (CSR) initiatives in state-owned enterprises (BUMN) is the partnership program, specifically tailored for the development of micro, small, and medium enterprises (MSMEs). The goal is to foster sustainability, independence, and competitiveness among these enterprises, utilizing funds derived from BUMN profits. This research aims to investigate the implementation of the CSR program and the long-term impacts it has on the company, with a specific focus on PT. Pertamina Gas. The research employs a qualitative approach utilizing descriptive research methods. Within this study, the researcher adopts one of Ralph Tench's theories and introduces a theoretical model that addresses the primary communication factors for CSR from the company's perspective. This model aims to answer the question, 'How can CSR communication be carried out more effectively?' The model comprises four key elements: communication, subject of communication, form of communication, and content of communication